Menggapai Efektivitas: Analisis Evaluasi Pelatihan dan Pasca Pelatihan BUMDesa di Jawa Barat - Widyanto Ramadhan; Wijayanti, Christina Intan (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2024)
Village-Owned Enterprises (Badan Usaha MilikDesa) are village businesses managed by the Village Government, and are legal entities. The Village Government can establish a Village-Owned Enterprise according to the Village's needs and potential. In establishing BUMDesa, human resources are needed who can manage BUMDesa so that it can provide profits and benefits to the community. With BUMDesa training, it is hoped that administrators can apply the knowledge gained in accordance with existing regulations. To see the success of the training results, a post-training evaluation was carried out for trainers, organizers, training alumni, non-alumni and BUMDesa institutions using the CIPP (Contex, Input, Process and Product) method. Technical data analysis is carried out when all data has been obtained in order to draw conclusions from the evaluation that has been carried out. The analysis model used is quantitative data analysis using descriptive techniques. Evaluation is carried out on training (output) and post-training (outcome). From the results of the training evaluation, the results obtained were: Guides/trainers got a score of 63.89 (good category), organizers got a score of 66.40 (good category), training graduates got a score of 74.39 (good category). Overall, the results of the training evaluation got a score of 68.23 (good category). From the results of the post-training evaluation carried out, the results were: for training alumni, they got a score of 55.02 (quite good). For the institution where the training alumni came from, they got a score of 51.24 (quite good). Overall the results of the post-training evaluation received a score of 53.13 (quite good). From these results the final results of the training evaluation and post-training evaluation received an average score of 60.68 (quite good). Keywords: BUMDesa; training evaluation; post training evaluation; CIPP method